Teacher Education Evaluation
XVIII, 174 p.
Keywords: In an age that dictates accountability and verifiability of educational programs, institutions of higher education are called on to justify their programs. To meet these demands, there is a need for improved methods for the evaluation of teacher education programs. More importantly, there is a need for the development of methods and procedures to conduct continuous and on-going evaluation that can aid the process of program improvement. Many institutions have had difficulties in developing and implementing satisfactory systems for conducting needed evaluation. In recent years the standards for the approval of teacher education programs in all of the states were strengthened as were the standards for approval by the National Council for the Accreditation of Teacher Education (NCATE). These revised standards put even more emphasis on accountability and the need for both summative and formative evaluation in a teacher education program. Tennessee Technological University has long been recognized as an institution with an exemplary project in program evaluation. As a result, in 1986, the state of Tennessee established at Tennessee Technological University, a Center for Teacher Education Evaluation. The Center began work in July 1986, on the development of models and systems for conducting teacher education program evaluation. To most, teacher education program evaluation is simple and straightforward. Evaluation includes a set of options, a set of criteria, data collection and interpretation, x and then use in meeting accountability needs.